Corporate governance regulatory framework in Zambia: recommendations for improvement - Luwabelwa, Walubita (School For Advanced Legal Studies, 2026)
Formulating an effective regulatory framework for a country is a tasking exercise even to the finest policy maker. It calls for an appreciation of the intricate social, cultural and economic nuances of a country so as not to divorce the legal and institutional framework from the people the framework is meant to serve. This dissertation considers the legal and institutional framework of corporate governance in Zambia. It argues in favour of a contextualised study of corporate governance in Zambia due to the country's high poverty levels, favourable geographical location for trade, and unfavourable capital structures of public listed companies, among other reasons. Several weaknesses in the current corporate governance framework are identified. These include the weak institutional capacity of private regulatory bodies, lack of a proper legal framework of self regulatory organisations, and the large number of small and medium enterprises, mining companies and state owned enterprises that fall outside the purview of corporate governance regulation. More importantly, the dissertation undertakes a comparative analysis of selected corporate governance themes in South Africa, United States of America and the United Kingdom. Based on this comparative analysis, it makes recommendations for improvement of corporate governance in Zambia. It suggests a balanced mix of a prescriptive and enabling approach to corporate governance regulation in Zambia. In particular, it recommends that the Zambian Companies Act should be amended to provide for key corporate governance aspects. The dissertation however cautions against over regulation beyond what is necessary for Zambia's needs, and frowns upon adopting a 'one-size-fits-all' approach to corporate governance in Zambia.